Pengaruh Jumlah Uang Beredar dan BI Rate Terhadap Tingkat Inflasi di Indonesia Periode Tahun 2010-2023 - Ian Saragih; Jonathan Brando Saragi; Tio Nardo Gulo; Fitrawaty Fitrawaty (CV. Ulil Albab Corp, 2024)
This study investigates the influence of the Money Supply (M2) and the BI RATE on the inflation rate in Indonesia from 2010 to 2023. Multiple linear regression analysis is employed to determine the significance of the effects both simultaneously and partially. The results indicate that M2 and the BI RATE have a significant simultaneous impact on inflation. While the BI RATE has a positive and significant effect on inflation, M2 does not show a significant impact according to the partial analysis. These findings suggest that, in the context of the Indonesian economy, an increase in the money supply does not always have a direct effect on inflation, highlighting the importance of the BI RATE in monetary policy for inflation control.